Evaluation of LMS Moodle Use in English Literature Classes - Meiga Ratih Tirtanawati; Chyntia Heru Woro Prastiwi (Ideas Publishing, 2022)
English literature plays an important role in language teaching at the university level, especially in the context of teaching English as a foreign language (EFL or English as a Foreign Language) for non-native English speakers such as students from the English Education Study Program. Even though, several studies have proven that literary works can improve students English skills (Novianti, 2016). So far, the lecture process for English Literature courses is carried out offline through face-to-face in class. However, since the Covid-19 pandemic has plagued Indonesia, especially in 2021, the English Literature course at IKIP PGRI Bojonegoro must be designed online using the Moodle platform. The research method used is descriptive. Data obtained are qualitative data. The data collected in this study include information data about the condition of students viewed from the qualitative aspect. With a focus on evaluating MOODLE-based online learning for teaching English Literature courses, this study presents the difficulties and strategies faced by lecturers and students involved in online English Literature lectures, as well as evaluating student difficulties in completing the final project in the form of monologue video. The use of LMS Moodle as a platform in teaching English Literature brings positive results. Moodle gives ease and assists the students difficulties in doing monologue performance videos as their final project of English Literature. In the end, this research is expected to be able to contribute in the form of presenting an online learning model for English Literature. English literature memegang peranan penting dalam pengajaran bahasa di tingkat universitas, terutama dalam konteks pengajaran bahasa Inggris sebagai bahasa asing (EFL atau English as a Foreign Language) bagi penutur bahasa Inggris non-pribumi seperti mahasiswa dari Program Studi Pendidikan Bahasa Inggris. Padahal, beberapa penelitian telah membuktikan bahwa karya sastra mampu meningkatkan kemampuan bahasa Inggris siswa (Novianti, 2016). Selama ini proses perkuliahan untuk mata kuliah English literature dilakukan secara offline melalui tatap muka di kelas. Namun sejak pandemi Covid-19 melanda Indonesia khususnya pada tahun 2021, maka mata kuliah English literature di IKIP PGRI Bojonegoro harus didesain secara online menggunakan platform MOODLE. Metode penelitian yang digunakan adalah deskriptif. Data yang diperoleh adalah data kualitatif. Data yang dikumpulkan dalam penelitian ini meliputi data informasi tentang kondisi siswa dilihat dari aspek kualitatif. Dengan fokus mengevaluasi pembelajaran online berbasis MOODLE untuk pengajaran mata kuliah Sastra Inggris, penelitian ini menyajikan kesulitan dan strategi yang dihadapi oleh dosen dan mahasiswa yang terlibat dalam perkuliahan English literature online, serta mengevaluasi kesulitan mahasiswa dalam menyelesaikan tugas akhir berupa video monolog. Penggunaan LMS MOODLE sebagai platform dalam pengajaran English literature membawa hasil yang positif. MOODLE memberikan kemudahan dan membantu kesulitan mahasiswa dalam mengerjakan video performance monolog sebagai tugas akhir mereka. Pada akhirnya, penelitian ini diharapkan dapat memberikan kontribusi berupa penyajian model pembelajaran Sastra Inggris secara online.